Exploring The Impact Of Per Capita Income And Population Size On VAT Revenue In APEC Member Countries - Muhammad Hafiz Fadhilah; Suparna Wijaya (Educoretax, 2023)
This research aims to evaluate how per capita income and population size impact Value Added Tax (VAT) revenue, considering corruption control variables as moderating factors. VAT revenue is the dependent variable in this study, while per capita income and population size are the independent variables. The influence of corruption control variables is also explored as interacting with the independent variables in affecting VAT revenue. The data used is sourced from World Bank Data, covering the period from 2008 to 2020. The analytical method employed is panel data regression using the panel-corrected standard error (PCSE) model. The research results indicate that per capita income has a negative influence on VAT revenue, meaning that as a country's per capita income increases, VAT revenue tends to decrease. Meanwhile, population size has a positive impact on VAT revenue, indicating that as a country's population size grows, VAT revenue tends to increase. Furthermore, it is found that the influence of corruption control variables interacts with per capita income. This interaction strengthens its impact on VAT revenue. However, when corruption control variables interact with population size, their influence on VAT revenue becomes weaker.